PERSONAL HYGIENIC PRACTICES OF SCHOOL GOING ADOLESCENTS – A CROSS SECTIONAL STUDY IN CHENNAI - Rani, M. A; Sathiyasekaran, BWC (Indian Journal of Community Health, 2013)
As per World Health Organization estimates, acute diarrhoeal diseases and respiratory infections are the leading causes of death among children1. Diarrhoeal diseases kill nearly 2 million children every year2. Repeated diarrhoeal episodes during childhood and adolescence can lower the fitness and productivity during adulthood3. The main source of diarrhoeal pathogens is the human faeces and for transmission of these faecal pathogens from one infected host to other contaminated hands plays an important role. Hygiene education and hand washing with soap are proved to be cost effective primary preventive measure for diarrhoeal diseases4.